Implementasi Pembelajaran Kecerdasan Spiritual untuk Mengaktualisasikan Nilai-Nilai Islam: Implementation of Spiritual Intelligence Learning to Actualize Islamic Values - Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to determine the extent of the implementation of learning spiritual intelligence and what are the factors supporting and inhibiting. In collecting the data, the writer used observation, interview and documentation. As for the analysis, the writer uses descriptive qualitative analysis techniques, namely the form of the data is written or spoken of observed behavior and so in this case the author seeks to undertake research which describes the overal nature of the real situation on the ground. The process of data analysis was conducted by researches through the stages of data reduction, data display, and conclution drawing ang verification. To check the validity of the data, the authors use the technique of persistant observation and triangulation.The results of this study it can be concluded that the implementation of learning spiritual intelligence delivered by using a variety of methods. Learning strategies in the plan include spiritual intelligence curriculum, bringing together the vision and mission of the school and parents, teaching practices, and monitoring. To find out the results of their study, using techniques such as charging achievement cards, daily grades, final grades and records. Supporting factors are appropriate curriculum, qualified teachers and good environment. While inhibiting factor is the difference in the vision and mission, the advancement of technology and the lack of instructional time.